1987
DOI: 10.1126/science.2443975
|View full text |Cite
|
Sign up to set email alerts
|

A System for Rapid DNA Sequencing with Fluorescent Chain-Terminating Dideoxynucleotides

Abstract: A DNA sequencing system based on the use of a novel set of four chain-terminating dideoxynucleotides, each carrying a different chemically tuned succinylfluorescein dye distinguished by its fluorescent emission is described. Avian myeloblastosis virus reverse transcriptase is used in a modified dideoxy DNA sequencing protocol to produce a complete set of fluorescence-tagged fragments in one reaction mixture. These DNA fragments are resolved by polyacrylamide gel electrophoresis in one sequencing lane and are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
380
0
13

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 779 publications
(396 citation statements)
references
References 18 publications
3
380
0
13
Order By: Relevance
“…The fragments containing vectors were sequenced using the chain termination dideoxy method. 27 Southern blot. 9 ml of each PCR reaction were separated in a 2% agarose gel and afterwards transfered onto a nylon membrane by capillary blot.…”
Section: Glycerol-3-phosphate Dehydrogenase (Gpdh) Measurementmentioning
confidence: 99%
“…The fragments containing vectors were sequenced using the chain termination dideoxy method. 27 Southern blot. 9 ml of each PCR reaction were separated in a 2% agarose gel and afterwards transfered onto a nylon membrane by capillary blot.…”
Section: Glycerol-3-phosphate Dehydrogenase (Gpdh) Measurementmentioning
confidence: 99%
“…Positive clones were identified from each isolate that contained inserts from 2.5 to 3.1 kb in size. The 3' 2400 bases of a 3.1 kb cDNA clone from the NADC isolate and a 3.0 kb cDNA clone of the KCD isolate were sequenced (Tabor & Richardson, 1987;Sanger et al, 1977) using an automated nucleic acid sequencer (Smith et al, 1986;Prober et al, 1987). When compared to the published sequence of the CFI/68 isolate of FCV (Neill et al, 1991), the nucleotide sequences of the NADC and KCD isolates were 81% and 79 % similar to the CFI/68 isolate.…”
mentioning
confidence: 99%
“…Furthermore, steadystate kinetic studies have identified hyperthermophilic DNA polymerase residues important for polymerization and exonuclease activities and for nucleotide binding (18,29,(31)(32)(33)(34)(35). Nucleotide analogs have also been important in identifying dNTP recognition determinants important in the polymerase reaction (32)(33)(34)(35)(36) and have proven useful in a variety of molecular biology applications, such as DNA sequencing and detection of single nucleotide polymorphisms (37)(38)(39)(40)(41). One group of analogs, 9-[(2-hydroxyethoxy)methyl]X triphosphates (where X is adenine, cytosine, guanine, or thymine; acyNTPs), 1 is particularly intriguing due to the wide spectrum of incorporation efficiency noted in different DNA polymerases, even within the same family of polymerase.…”
mentioning
confidence: 99%